Surface specificity and mechanistic pathway of de-fluorination of C60F48 on coinage metals. Issue 10 (10th September 2020) - Palacios-Rivera, Rogger; Malaspina, David C.; Tessler, Nir; Solomeshch, Olga; Faraudo, Jordi; Barrena, Esther; Ocal, Carmen
Abstract : Depending on the metal, C60 F48 molecules lose all the fluorine atoms and transform to C60 at room temperature. Molecular dynamics simulations with ReaxFF reactive force field provide a detailed mechanistic picture of the surface-induced de-fluorination. Abstract : We provide experimental and theoretical understanding on fundamental processes taking place at room temperature when a fluorinated fullerene dopant gets close to a metal surface. By employing scanning tunneling microscopy and photoelectron spectroscopies, we demonstrate that the on-surface integrity of C60 F48 depends on the interaction with the particular metal it approaches. Whereas on Au(111) the molecule preserves its chemical structure, on more reactive surfaces such as Cu(111) and Ni(111), molecules interacting with the bare metal surface lose the halogen atoms and transform to C60 . Though fluorine–metal bonding can be detected depending on the molecular surface density, no ordered fluorine structures are observed. We show the implications of the metal-dependent de-fluorination in the electronic structure of the molecules and the energy alignment at the molecule–metal interface. Molecular dynamics simulations with ReaxFF reactive force field corroborate the experimental facts and provide a detailed mechanistic picture of the surface-induced de-fluorination, which involves the rotation of the molecule on the surface. Outstandingly, a thermodynamic analysis indicates that the effect of the metal surface is lowering and diminishing the energy barrier for C–F cleave, demonstrating the catalytic role of the surface. The present study contributes to in-depth knowledge of the mechanisms that affect the degree of stability of chemical species on surfaces, which is essential to advance our understanding of the chemical reactivity of metals and their role in on-surface chemical reactions.